Entropy engineering promotes thermoelectric performance in p-type chalcogenides - Binbin Jiang (Nature Portfolio, 2021)
The synergism of entropy engineering and the typical optimization mechanisms in high-entropy-stabilized chalcogenide is unknown. Here, the authors find high-entropy-stabilized composition works as a promising matrix of applying synergistic effect to realize high thermoelectric performance.